Proceedings of the 59th Annual Meeting of the Association for Computational Linguistics and the 11th International Joint Confer 2021
DOI: 10.18653/v1/2021.acl-long.269
|View full text |Cite
|
Sign up to set email alerts
|

Towards Emotional Support Dialog Systems

Abstract: Emotional support is a crucial ability for many conversation scenarios, including social interactions, mental health support, and customer service chats. Following reasonable procedures and using various support skills can help to effectively provide support. However, due to the lack of a well-designed task and corpora of effective emotional support conversations, research on building emotional support into dialog systems remains untouched. In this paper, we define the Emotional Support Conversation (ESC) task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 30 publications
0
69
0
Order By: Relevance
“…Table 3 shows the dialogue safety classification results of four baseline models and the three variants of Canary ( §4.1). With initial T5 weights of Delphi (Jiang et al, 2021), our Canary outperforms all baseline models. This shows that Delphi delivers the knowledge on common patterns of human moral sense for short snippets of everyday situations, which can provide valuable information for determining ethical implications under dialogue setup.…”
Section: Dialogue Safety Classification Via Canarymentioning
confidence: 96%
See 1 more Smart Citation
“…Table 3 shows the dialogue safety classification results of four baseline models and the three variants of Canary ( §4.1). With initial T5 weights of Delphi (Jiang et al, 2021), our Canary outperforms all baseline models. This shows that Delphi delivers the knowledge on common patterns of human moral sense for short snippets of everyday situations, which can provide valuable information for determining ethical implications under dialogue setup.…”
Section: Dialogue Safety Classification Via Canarymentioning
confidence: 96%
“…Additionally, other works have tackled the problem of detecting and explaining whether a situation was toxic or unethical, but not in multi-turns dialogues (Jiang et al, 2021;Forbes et al, 2020;Zhao et al, 2021;Hendrycks et al, 2021;Qiu et al, 2022;Zhang et al, 2022a;Ziems et al, 2022).…”
Section: Related Workmentioning
confidence: 99%
“…[32] generate meaningful responses with a coherent structure for a post, and express the desired emotion within a unified framework. GLHG [33] aims to capture the global cause, local intentions and dialog history, and model hierarchical relationships between them in the emotional support conversation [34]. However, in psychology, the fundamental reason why human beings behave in the external world is that they take motivation as the starting point.…”
Section: Related Workmentioning
confidence: 99%
“…Empathy is a desirable trait of human daily conversations that enables individuals to understand, perceive, and respond appropriately to the situation and feelings of others (Keskin 2014). Previous research has demonstrated that empathetic dialogue systems can improve user experience and satisfaction in multiple domains (Fitzpatrick, Darcy, and Vierhile 2017;Liu et al 2021;Wang et al 2021). Hence, it is important to discover ways that allow us to equip open-domain dialogue systems with empathy.…”
Section: Introductionmentioning
confidence: 99%